2015
DOI: 10.1021/acsami.5b04305
|View full text |Cite
|
Sign up to set email alerts
|

Anodic, Cathodic, and Annihilation Electrochemiluminescence Emissions from Hydrophilic Conjugated Polymer Dots in Aqueous Medium

Abstract: Hydrophilic poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene] (MEH-PPV) conjugated polymer dots (CP-dots) capped by Triton X-100 were synthesized. For the first time, the electrochemiluminescence (ECL) emission of CP-dots was investigated in aqueous solution. At the glassy carbon/water interface, the CP-dots have excellent and multichannel ECL properties, such as having annihilation ECL activity in the absence of coreactants, and give bright anodic and cathodic ECL emission (590 nm) in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 37 publications
0
39
1
Order By: Relevance
“…Recently, several research groups have reported ECL in other Pdots 50 and CPNs 4749,53 composed of different semiconducting polymers. They also applied ECL Pdots or CPNs as sensors.…”
Section: Electrochemiluminescent and Chemiluminescent Pdots And Cpnsmentioning
confidence: 99%
“…Recently, several research groups have reported ECL in other Pdots 50 and CPNs 4749,53 composed of different semiconducting polymers. They also applied ECL Pdots or CPNs as sensors.…”
Section: Electrochemiluminescent and Chemiluminescent Pdots And Cpnsmentioning
confidence: 99%
“…[45] Chi and co-workersd eveloped many polymers capped with Triton X-100 for better ECL behavior. [39] In all, PDots represent avital part of ECL materials.I tisrecommended that AIE experimentss hould be added to help authors understand if AIECL is active in these systems.…”
Section: Polymer Dots (Pdots)mentioning
confidence: 99%
“…Besides the above PDots, there are many other PDots that might be underestimated because of the method of PDots formation. After synthesis of polymer molecules, many techniques such as reprecipitation, ultrasonication, microemulsion have been applied in forming nanoparticles with various morphologies. This procedure makes polymers aggregate into dots with a certain shape and size.…”
Section: Aiecl Luminophoresmentioning
confidence: 99%
See 1 more Smart Citation
“…To get insight into the hydrophilic/hydrophobic effects of Pdots on the ECL behaviors, Chi et al gave a detailed comparison experiments on this issue. [114] They adopted poly[2-methoxy-5-(2-ethylhexyloxy)-1,4phenylenevinylene] (MEH-PPV) conjugated polymer dots (CPdots) with and without the nonionic surfactant Triton X-100 as ECL sensors. As presented in Figure 7C, the bare CP-dots which show hydrophobic feature do not give any ECL or CV peak.…”
Section: Quantum Dotsmentioning
confidence: 99%